Measurement of the tau lepton polarisation at LEP2 - Abdallah, J; Abreu, P; Adam, W; Adzic, P; Albrecht, T; Alemany-Fernandez, R; Allmendinger, T; Allport, P; Amaldi, U; Amapane, N; Amato, S; Anashkin, E; et al. (2008)
A first measurement of the average polarisation Pτ of tau leptons produced in e+e- annihilation at energies significantly above the Z resonance is presented. The polarisation is determined from the kinematic spectra of tau hadronic decays. The measured value Pτ = - 0.164 ± 0.125 is consistent with the Standard Model prediction for the mean LEP energy of 197 GeV. © 2007 Elsevier B.V. All rights reserved.